Sistemas urbanos de água e esgoto: princípios e indicadores de sustentabilidade - Miranda, Aline Branco de (Universidade Federal de São Carlos, 2003)
An adequate management of the water supply and sewerage urban systems can reduce several negative impacts. It can also bring positive results to the environment, society and economy. The concept of sustainability tries to incorporate these concerns. In order to be effectively applied it is necessary a change in the perception of the use of water, followed by the adoption of monitoring instruments. In this work, it was attempted to establish specific principles of sustainability which can be applied to the referred systems, according to the generic principles found in the literature. It was also proposed indicators to be used as monitoring instruments. These indicators were established based on a restrict selection assisted by some researchers in this area. Later it was made an enlarged selection from a shared process in the town of Jaboticabal (SP). Finally, the use of the selected indicators made in the town of Jaboticabal, allowed the identification of the problems and then there was the orientation to public policies for this sector.
Keywords: Abastecimento de água; Indicadores urbanísticos; Água - sistemas urbanos; Sustentabilidade; ENGENHARIAS::ENGENHARIA QUIMICA::TECNOLOGIA QUIMICA::AGUA